(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This paper has explored the issue of women in sales leadership with emphasis on organisational, cultural and structural impediments that prevent women from rising to the sales management roles in Nigeria. The research used a convergent mixed-methods methodology, which was a combination of a national stratified survey including about 450 sales professionals, 30 semi-structured interviews and three company case studies. The research model involved the analysis of the probability of promotion through logistic regression and the thematic analysis to test the lived experiences of the participants. Results, derived through a review of available literature and pilot data, showed that sponsorship and institutionalised human resources tracks are important factors in diminishing gender inequity in promotion. Moreover, flexible role design is demonstrated to enhance retention and promote women with caregiving duties more. The article ends by presenting policy implications and recommendations that the firm-level practices should be geared towards putting in place quantifiable and sustainable channels for women moving to sales leadership roles.